Fatores de risco para o declínio da mobilidade durante a caminhada em idosos institucionalizados - Araújo, José Rodolfo Torres de (2022)
Mobility during walking represents a basic human need that is essential for maintaining quality of life and, when impaired, requires multiprofessional support. The present study aimed to identify the prevalence of mobility limitations and associated factors and to analyze the trajectory of changes in mobility during walking (ie, maintenance, recovery or decline) of institutionalized older adults and to verify the incidence and risk factors for decline of mobility. Two studies were carried out, the first cross-sectional with a sample of 305 older adults and the second a longitudinal study, of the prospective cohort type, with a sample of 358 older adults at baseline, developed over two years in ten long-stay institutions for elderly (ILPI) in the city of Natal-RN, northeast of Brazil. In both studies, mobility was assessed using the item “walking” of the Barthel Index. The chi-square test (first and second study), multiple logistic regression (first study) and Poisson regression (second study) were used. Multiple logistic and Poisson regression were used to build a multiple model. The first study identified a prevalence of mobility limitation in older adults of 65.6% (95% confidence interval [CI], 59.6-70.4), being associated with malnutrition/risk of malnutrition (1.86, CI 95%, 1.54 to 2.26, P < 0.001) and age ≥81 years (1.35, 95% CI, 1.12 to 1.63, P = 0.002). The second study showed that the incidence of mobility decline was 10.6% (95% CI: 7.4 - 13.8) in 12 months and 37.7% (95% CI: 18.0 – 40.0) in 24 months. The risk factors for decline were: age ≥83 years (RR: 1.58; 95% CI: 1.25 – 2.02; p<0.001) and hospitalization (RR: 3.16; 95% CI: 1.55 – 6.45; p=0.002). The mobility maintenance rate was 31.8% (95% CI: 31.8 -42.9) at 12 months and 23.2% (95% CI: 26.8 - 38.5) at 24 months , and the improvement rate, 2.5% (95% CI: 1.0 – 5.0) and 1% (95% CI: 0.2 - 2.6), at 12 and 24 months, respectively. It is concluded that mobility limitation had a high prevalence among the older adults residing in ILPI in Brazil and was associated with advanced age and deficient nutritional status. On the other hand, the mobility trajectory during the walk of institutionalized older adults in northeastern Brazil was dynamic (ie, increased incidence of mobility decline after 24 months) and associated with advanced age and hospitalization.